Pengaruh minuman popping boba terong belanda dengan ekstrak teh hijau terhadap tes toleransi glukosa oral - Mudiati Nisa Utami; A’immatul Fauziyah; Luh Desi Puspareni (UHAMKA PRESS, 2021)
Tamarillo popping boba drinks with green tea extract is an alternative product that has been developed which has a high antioxidant content of phenolic compounds so it can reduce blood glucose levels. The purpose of this study was to analyze the effect of tamarillo popping drink with the addition of green tea extract on post-prandial blood glucose levels. This study used an experimental study design method with 11 healthy adults as the subject. There were two groups in this study i.e the control group who only consumed glucose solution and the treatment group who consumed glucose solution together with the tamarillo popping drink with the addition of green tea extract. Measurement of blood glucose response was performed using the Oral Glucose Tolerance Test (OGTT) method. The results of the intervention showed that the average blood glucose level in the treatment group was lower than the control group. The results of the paired t-test broad AUC also showed that the treatment group was significantly different and lower than the control group. The results of the% PKGD calculation were 13.63%. Thus, it can be concluded that giving boba popping drink with the addition of green tea extract is effective in reducing blood glucose levels.